Export of Higher Education: Innovations in Physical Education Practice - M. G. Minin; E. O. Frantcuzskaia; A. S. Minich; K. A. Smyshlyaev; A. V. Smyshlyaev (Moscow Polytechnic University, 2020)
Creating conditions for the export potential is one of the drivers for the development of the domestic higher education. All the factors of socio-cultural adaptation of foreign students are to be identified in order to build a world-class educational background in Russian universities. The potential of physical education to solve the problems of foreign student integration into the Russian social environment is an urgent area of modern pedagogical research. The article presents the authors' vision of organizational and pedagogical methods to transform physical education practice at university and to designate some new types of professional teaching activities of a physical education instructor. The research centered in the following Tomsk universities: Siberian State Medical University, National Research Tomsk Polytechnic University, and Tomsk State Pedagogical University. The international component in the educational ecosystem development in Tomsk Region is outlined in the field of the regional project to create the Big University. The applied methods for the research involved analysis of theoretical sources, surveys, observations, product analysis, and the expert assessment method.